2003
DOI: 10.1007/s00253-003-1233-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and identification of genes essential for dimethyl sulfide utilization in Pseudomonas putida strain DS1

Abstract: Microbial dimethyl sulfide (DMS) conversion is thought to be involved in the global sulfur cycle. We isolated Pseudomonas putida strain DS1 from soil as a bacterium utilizing DMS as a sole sulfur source, and tried to elucidate the DMS conversion mechanism of strain DS1 at biochemical and genetic level. Strain DS1 oxidized DMS to dimethyl sulfone (DMSO(2)) via dimethyl sulfoxide, whereas the oxidation was repressed in the presence of sulfate, suggesting that a sulfate starvation response is involved in DMS util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 42 publications
1
53
0
Order By: Relevance
“…putida strain DS1, which utilized DMS or DMSO as a sulfur source, was recently isolated (Endoh et al, 2003). When strain DS1 grew on DMS as a sulfur source, DMSO and dimethyl sulfone (DMSO 2 ) accumulated in the culture.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…putida strain DS1, which utilized DMS or DMSO as a sulfur source, was recently isolated (Endoh et al, 2003). When strain DS1 grew on DMS as a sulfur source, DMSO and dimethyl sulfone (DMSO 2 ) accumulated in the culture.…”
Section: Introductionmentioning
confidence: 99%
“…DMS-utilization-defective mutants of strain DS1 were obtained by Tn5 mutagenesis. One mutant, Dfi175, no longer utilized DMS, DMSO, DMSO 2 and MSA as sulfur sources, and had a deficiency in the ssuEADCBF operon, which encodes an ABC-transporter (SsuABC), a two-component sulfonate sulfonatase system (SsuED) and a small protein SsuF (Endoh et al, 2003). The ssuEADCBF operon has also been reported to be essential in P. putida S-313 for utilization of organosulfur compounds, including sulfonates, sulfate esters and methionine (Kahnert et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transfers of pCAR1 to P. resinovorans CA10dm4 and P. putida KT2440 were detected experimentally at frequencies of 3 Â 10 À1 and 3 Â 10 À3 per donor cell, 57) suggesting that pCAR1 is in fact a self-transmissible plasmid. Mating experiments showed that pCAR1 can transfer from P. putida HS01 (P. putida DS1 85) harboring pCAR1) to P. chlororaphis, P. fluorescens, and P. stutzeri, although no transfer of pCAR1 from P. resinovorans CA10 to them was detected. 86) Hence we concluded that the recipient range of pCAR1 was affected largely by the donor cell.…”
Section: Conjugal Transfermentioning
confidence: 99%